Key money (badl al-khulu): an Islamic perspective - Habibur Rahman, Muhammad; Osmani, Noor Mohammad (State Islamic University (UIN) Ar Raniry Banda Aceh Indonesia, 2018)
The key money (badl al-khulu) refers to the amount that one pays to the other who forgoes his/her right to enjoy the usufruct of the real estate like house, shop and others. This paper intends to study the legal status of exchanging key money from the perspective of Islamic law. The study is qualitative in nature and an analytical method is employed to accomplish the study based on both classical and modern references of the topic. The study finds that the exchange of key money could be between the tenant and the landlord or between the current tenant and the subsequent tenant, or among all these three parties. If the exchange of key money is made during the lease period then it is permissible. However, if it is made after expiry of lease period then it is invalid because after termination of the right of tenant the landlord is more entitled to his/her possessions and he/she may do whatever wishes. Nevertheless, if the landlord consents to the exchange of key money, and the tenant makes a new lease agreement with him, then the exchange of key money is valid despite the expiry of the lease period.